2008
DOI: 10.1017/s0007114508992564
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an association between genetic variants of thefatty acid desaturase 1 fatty acid desaturase 2(FADS1 FADS2) gene cluster and the fatty acid composition of erythrocyte membranes

Abstract: The present study gives further evidence for the recently found association between variants of the fatty acid desaturase 1 fatty acid desaturase 2 (FADS1 FADS2) gene cluster and PUFA in blood phospholipids and explores this association for cellular fatty acids in erythrocyte membranes. In a subgroup of adults participating in the Bavarian Nutrition Survey II, a cross-sectional population-based study conducted in Bavaria, Germany, allelic variation in three selected loci of the FADS1 FADS2 gene cluster was ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
132
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(150 citation statements)
references
References 28 publications
13
132
1
Order By: Relevance
“…Presently, 20:2n-6 and 20:3n-3 are widely considered dead-end products, in part because their conversion to LCPUFA has not been unequivocally established (43). However, recent studies have associated 20:2n-2 with FADS2 polymorphisms and/or fatty acid compositions in humans (32,44), including patients with cardiovascular disease (31) and type 2 diabetes mellitus (45). In addition, apolipoprotein D knockout mice, a model for psychiatric disorders, show increased CNS 20:2n-6 and 18:2n-6 compared with wild-type mice (46).…”
Section: Discussionmentioning
confidence: 99%
“…Presently, 20:2n-6 and 20:3n-3 are widely considered dead-end products, in part because their conversion to LCPUFA has not been unequivocally established (43). However, recent studies have associated 20:2n-2 with FADS2 polymorphisms and/or fatty acid compositions in humans (32,44), including patients with cardiovascular disease (31) and type 2 diabetes mellitus (45). In addition, apolipoprotein D knockout mice, a model for psychiatric disorders, show increased CNS 20:2n-6 and 18:2n-6 compared with wild-type mice (46).…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis that they play a key role in inflammatory diseases is strengthened by functional studies in mice, where selective D5D and D6D inhibitors showed an anti-inflammatory response. Several single nucleotide polymorphisms (SNP) in FADS genes were reported in humans, and some showed association between FADS SNPs and fatty acids in serum or plasma phospholipids, and erythrocyte membrane and adipose tissue (Schaeffer et al 2006, Malerba et al 2008, Rzehak et al 2009), demonstrating that these concentrations are influenced not only by diet, but also to a large extent by genetic variants common in the world population (Koletzko et al 2011).…”
Section: Polymorphismsmentioning
confidence: 99%
“…A third putative desaturase gene, FADS3 , is located in the 6.0 kb telomeric side from the FADS2 gene in a tail-to-tail orientation ( 18 ). Several candidate gene studies reported an association of a number of single nucleotide polymorphisms (SNPs) in the FADS gene cluster with fatty acid composition in human tissues (19)(20)(21)(22). These results were strengthened recently by our study, which for the fi rst time compared genome-wide SNP data with metabolomics data and replicated the previous fi ndings by this new approach ( 23 ).…”
Section: Luciferase Reporter Assaysmentioning
confidence: 99%